Oral midodrine is comparable to albumin infusion in cirrhotic patients with refractory ascites undergoing large-volume paracentesis: results of a pilot study. Issue 3 (March 2019) - Yosry, Ayman; Soliman, Zeinab A.; Eletreby, Rasha; Hamza, Iman; Ismail, Alaa; Elkady, Mohammad A.
Abstract : Background and aims: Albumin infusion reduces the incidence of postparacentesis circulatory dysfunction among patients with cirrhosis and tense ascites compared with no treatment. Less costly treatment alternatives such as vasoconstrictors have been investigated, but the results are controversial. Midodrine, an oral α1-adrenergic agonist, increases effective circulating blood volume and renal perfusion by increasing systemic and splanchnic blood pressure. Our aim is to assess whether or not morbidity in terms of renal dysfunction, hyponatremia, systemic, or portal hemodynamics derangement or mortality differed in patients receiving albumin versus midodrine. Patients and methods: Seventy-five patients with cirrhosis and refractory ascites were randomized to receive albumin infusion, oral midodrine for 2 days, or oral midodrine for 30 days after therapeutic large volume paracentesis (LVP). The primary endpoints were development of renal impairment or hyponatremia, change in systemic and portal hemodynamics, cost, and mortality in the short-term and long-term follow-up. Results: No significant difference was found between groups in the development of renal impairment, hyponatremia, or mortality 6 and 30 days after LVP. A significant increase in 24-h urine sodium excretion was noted in the midodrine 30-day group. Renal perfusion improved significantly with the midodrine intake for 30 days only. The cost of midodrine therapy was significantly lower than albumin. Conclusion: Midodrine is as effective as albumin in reducing morbidity and mortality among patients with refractory ascites undergoing LVP at a significantly lower cost. Long-duration midodrine intake can be more useful than shorter duration intake in terms of improvement of renal perfusion and sodium excretion.